1996
DOI: 10.1099/0022-1317-77-5-1019
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the domains on the phosphoprotein of bovine respiratory syncytial virus required for N-P interaction using a two-hybrid system

Abstract: Specific interactions between the nucleocapsid protein (N) and the phosphoprotein (P) of bovine respiratory syncytial virus (BRSV) have been investigated using a yeast-based two-hybrid system. Plasmids encoding the yeast GAL4 DNA binding domain fused with the N gene and GAL4 activation domain fused with the P gene were cotransfected into competent yeast cells. The ability of the N and P proteins to interact in vivo was measured by activation of the lacZ reporter gene by the GAL4 transactivation region. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 21 publications
2
22
0
1
Order By: Relevance
“…However, we cannot exclude the possibility that the P NTD binding site partially overlaps the P CTD binding site on N. Furthermore, although the N NTD is a globular, alpha-helical domain that should not undergo major conformational changes between N 0 and N-RNA forms, P NTD binding on N mono could induce a local conformational change that renders the P CTD binding site inaccessible. In any case, our results concerning the RSV N 0 -P NTD interaction are in agreement with data obtained previously with BRSV showing a direct interaction between P NTD (residues 1 to 40) and N using the yeast two-hybrid system (20). Since P and N are highly conserved between BRSV and HRSV, it is likely that P NTD is the main N 0 binding site for both viruses.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, we cannot exclude the possibility that the P NTD binding site partially overlaps the P CTD binding site on N. Furthermore, although the N NTD is a globular, alpha-helical domain that should not undergo major conformational changes between N 0 and N-RNA forms, P NTD binding on N mono could induce a local conformational change that renders the P CTD binding site inaccessible. In any case, our results concerning the RSV N 0 -P NTD interaction are in agreement with data obtained previously with BRSV showing a direct interaction between P NTD (residues 1 to 40) and N using the yeast two-hybrid system (20). Since P and N are highly conserved between BRSV and HRSV, it is likely that P NTD is the main N 0 binding site for both viruses.…”
Section: Discussionsupporting
confidence: 82%
“…3E). Our data showed that N mono copurified with GST-P and GST-P but not with GST-P [1][2][3][4][5][6][7][8][9][10], GST-P [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], GST-P , or GST-P . These results revealed that an N mono -specific binding site is located between amino acids 1 and 29 of P. It is noteworthy that residues 1 to 10, if not sufficient to interact with N mono , are required for the interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The N protein is present in large amounts in the virion and in infected cells and has several functions. In combination with P, L and possibly M2-2, the N protein is a major element of the nucleocapsid and protects the viral genome RNA from RNAse [93,112]. The N protein seems to play a role in the transition between the transcription and the replication phases of the viral RNA [93].…”
Section: Nucleocapsid Proteinsmentioning
confidence: 99%
“…In combination with P, L and possibly M2-2, the N protein is a major element of the nucleocapsid and protects the viral genome RNA from RNAse [93,112]. The N protein seems to play a role in the transition between the transcription and the replication phases of the viral RNA [93]. The P protein has 241 AA [2] and appears to act as a chaperone for soluble N and is implicated as a regulation factor for viral transcription and replication.…”
Section: Nucleocapsid Proteinsmentioning
confidence: 99%